I have a tricky question here....

Please just feed in any comment, anything you can spot that I can't

I have been asked to compare the formula of Sygma (k=1 until n value) of k, Sygma (k=1 until n value) of k(k+1) and Sygma (k=1 until n value) of k(k+1)(k+2)?

Hence comparing these...

Sygma (k=1 until n value) of k[/B] = 1/2 n(n+1)

Sygma (k=1 until n value) of k(k+1)[/B] = 1/3 n(n+1)(n+2)

Sygma (k=1 until n value) of k(k+1)(k+2) [/B] = 1/4 n(n+1)(n+2)(n+3)

**I have been asked to comment on these as much as I possibly can Can anyone help?**